Determination and diagnostic value of CA9 mRNA in peripheral blood of patients with oral leukoplakia - Torres López, Manuel (J Enzyme Inhib Med Chem, 2018)
Background: Oral leukoplakia is one of the most common oral premalignant disorder. The classical evaluation through tissue biopsy is not always valid to evaluate the risk of malignization. Material and methods: RT-qPCR was performed on 47 blood samples (21 patients with leukoplakia, 2 with oral squamous cell carcinoma (OSCC), and 24 healthy patients) and on 11 tissue samples (3 leukoplakia, 4 OSCC, and 4 samples of healthy tissue). Results: There are significant differences in expression between the different groups (F = 4.057, p = .006). The Duncan post hoc test shows that the only group that differentiates is the tumour tissue. Using Wilcoxon test, different covariables of patients with leukoplakia were analysed with respect to the group of healthy patients and no significant differences were observed. Conclusions: The diagnostic route through liquid biopsy has not been conclusive in this study, but there are significant differences in the levels analysed in the different tissue samples.